The Kursk Battle (July 5 — August 23, 1943): On Some Aspects of the Activities of the Military Command and Control Agencies of the Red Army Artillery Armament - V. A. Chernukhin (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article highlights the problematic aspects of managing the activities of the artillery armament service during the preparation and during the Battle of Kursk-one of the greatest battles not only of the Great Patriotic War of the Soviet people against Nazi Germany and its allies, but also of World War II as a whole. The topic of the article has an actual sound from the point of view of generalizing and analyzing the enormous work that the artillery armament service has made to achieve victory. The example of the Battle of Kursk shows that not only the unparalleled courage of the troops, the art of generals, but also a sufficient number of modern military equipment, weapons, ammunition, as well as the system of work of the relevant structures for supplying artillery, mortars and ammunition to military units connection) of constant combat readiness.